Covalently Crosslinked Hydrogels via Step‐Growth Reactions: Crosslinking Chemistries, Polymers, and Clinical Impact. Issue 25 (14th May 2021) - Gao, Yongsheng; Peng, Kevin; Mitragotri, Samir
Abstract: Hydrogels are an important class of biomaterials with the unique property of high‐water content in a crosslinked polymer network. In particular, chemically crosslinked hydrogels have made a great clinical impact in past years because of their desirable mechanical properties and tunability of structural and chemical properties. Various polymers and step‐growth crosslinking chemistries are harnessed for fabricating such covalently crosslinked hydrogels for translational research. However, selecting appropriate crosslinking chemistries and polymers for the intended clinical application is time‐consuming and challenging. It requires the integration of polymer chemistry knowledge with thoughtful crosslinking reaction design. This task becomes even more challenging when other factors such as the biological mechanisms of the pathology, practical administration routes, and regulatory requirements add additional constraints. In this review, key features of crosslinking chemistries and polymers commonly used for preparing translatable hydrogels are outlined and their performance in biological systems is summarized. The examples of effective polymer/crosslinking chemistry combinations that have yielded clinically approved hydrogel products are specifically highlighted. These hydrogel design parameters in the context of the regulatory process and clinical translation barriers, providing a guideline for the rational selection of polymer/crosslinking chemistry combinations to construct hydrogels with high translational potential are further considered. Abstract : Various polymers and crosslinking chemistries are utilized for fabricating hydrogels for translational research. However, selecting appropriate crosslinking chemistries and polymers for the intended clinical application is challenging and time‐consuming. The key features of crosslinking chemistries and polymers commonly used for preparing hydrogels are outlined and their performance in the context of the regulatory process and clinical translation barriers summarized.